Novel Extended Weibull Regression Model for Investigating the Survival Times of Breast Cancer Patients - Abdulkadir, Ahmed; Adubisi, Obinna Damian; Madaki, R. M. (Mikailalsys Journal of Mathematics and Statistics, 2024)
The new five-parameter alpha power generalized odd generalized exponentiated Weibull distribution is introduced, and some of its structural properties are derived. Its parameters are estimated by maximum likelihood, and a simulation study examines the accuracy of the estimates. A regression model is constructed based on the logarithm of the proposed distribution to investigate the survival times of breast cancer patients in Bauchi State, Nigeria. The applicability and flexibility of the novel model is proven by means of cancer dataset.